Holocene marine terraces as recorders of earthquake uplift: Insights from a rocky coast in southern Hawke's Bay, New Zealand. Issue 2 (13th November 2022) - Litchfield, Nicola; Morgenstern, Regine; Clark, Kate; Howell, Andy; Grant, Georgia; Turnbull, Jocelyn
Abstract: On rocky tectonic coasts, data from Holocene marine terraces may constrain the timing of coseismic uplift and help identify the causative faults. Challenges in marine terrace investigations include: (1) identifying the uplift datums; (2) obtaining ages that tightly constrain the timing of uplift; (3) distinguishing tsunami deposits from beach deposits on terraces; and (4) identifying missing terraces and hence earthquakes. We address some of these challenges through comparing modern beach sediments and radiocarbon ages with those from a trench excavated across three terraces at Aramoana, central Hikurangi Subduction Margin, New Zealand. Sedimentary analyses identified beach and dune deposits on terraces but could not differentiate specific environments within them. Modern beach shells yielded modern radiocarbon ages, regardless of position or species, showing age inheritance and habitat is likely not an issue when dating shells on these terraces. By integrating terrace mapping, stratigraphy, morphology, and radiocarbon ages we develop a conceptual model of coastal uplift and terrace formation following at least two, possibly three, earthquakes at 5490–5070, 2620–2180, and 950–650 cal. yr bp . A high step and time gap between the upper two terraces raises the possibility that at least one intervening terrace is completely eroded. The trench exposure also showed that terrace stratigraphy may differ from that inferred from surface geomorphology, with apparent beach ridges being of composite origin and draping of younger beach deposits on the outer edge of a previous terrace. Dislocation modelling and comparison of marine terrace and earthquake ages from ~4 km south and ≤ 73 km north confirms that the most likely earthquake source is the nearshore, landward‐dipping, Kairakau Fault. Alternative sources, such as multi‐fault ruptures of the Kairakau‐Waimārama faults or Hikurangi subduction earthquakes, and/or a combination of the two are also possible and should be examined in future studies. Abstract : On rocky tectonic coasts Holocene marine terraces record earthquake uplift but there are challenges such as identifying the uplift datum, accurate dating and missing terraces. These are addressed through comparing modern beach sediments and radiocarbon ages with those from a trench across terraces in the central Hikurangi Subduction Margin. A coeseismic terrace model, dislocation modelling and comparison of ages with other sites show uplift in three earthquakes most likely on upper plate faults, but subduction earthquakes are also possible.